Projection-Based Neighborhood Non-Negative Matrix Factorization for lncRNA-Protein Interaction Prediction - Ma, Yingjun; He, Tingting; Jiang, Xingpeng (Frontiers in Genetics, 2019)
Many long ncRNAs (lncRNA) make their effort by interacting with the corresponding RNA-binding proteins, and identifying the interactions between lncRNAs and proteins is important to understand the functions of lncRNA. Compared with the time-consuming and laborious experimental methods, more and more computational models are proposed to predict lncRNA-protein interactions. However, few models can effectively utilize the biological network topology of lncRNA (protein) and combine its sequence structure features, and most models cannot effectively predict new proteins (lncRNA) that do not interact with any lncRNA (proteins). In this study, we proposed a projection-based neighborhood nonnegative matrix decomposition model (PMKDN) to predict potential lncRNA-protein interactions by integrating multiple biological features of lncRNAs (proteins). First, according to lncRNA (protein) sequences and lncRNA expression profile data, we extracted multiple lncRNA (protein) features. Secondly, based on protein GO ontology annotation, lncRNA sequence data, lncRNA(protein) feature information, and modified lncRNA-protein interaction network, we calculate multiple similarities of lncRNA (protein), and fused them to obtain a more accurate lncRNA(protein) similarity network. Finally, combining the similarity and various feature information of lncRNA (protein), as well as the modified interaction network, we propose a projection-based neighborhood non-negative matrix decomposition algorithm to predict the potential lncRNA-protein interactions. On two benchmark datasets, PMKDN showed better performance than other state-of-the-art methods for the prediction of new lncRNA-protein interactions, new lncRNAs and new proteins. Case study further indicates that PMKDN can be used as an effective tool for lncRNA-protein interaction prediction.